PENGKAJIAN BUDIDAYA ULAT SAGU SEBAGAI SUMBER PROTEIN PAKAN TERNAK - Isa Nagib Edrus; Sjahrul Bustaman (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2007)
Assessment on Sago Larva Cultivation as a Protein Source of Feed. The area of sago crops in Moluccas is 31.360 ha with the number of sago tree ready to be harvested amounted 86 trees per ha. One of the wastes from harvesting sago crop is the tree sprouts which are not utilized and become places for coconut red beetles (Rhynchophorus ferrugenesis) to lay eggs. Larva from these beetles is known as sago larva, usually consumed by Moluccas and Papua societies. When the sago larvas become adults, they will transform into coconut beetles, which are pests for coconut crops. Research on potencies and cultivation techniques was conducted in 2006 with purposes to obtain: 1) natural and artificial cultivation techniques, 2) spawning time and season, and 3) nutrient value and potencies of sago larva. The estimation on potency was obtained from surveys at sago processing centers in South East Moluccas Regency, Central Moluccas Regency, and Western Seram. Cultivation techniques were differentiated between natural and artificial. Laboratory analysis was conducted to obtain the nutrient value and essential amino acid content. Statistical test was conducted on the data resulting from treatment comparisons. The result of the study shows that larva sago potency in Moluccas is estimated to be equal to 935 tons based on sago crop area, with a productivity of 2.52 kg/ m'. Spawning season is all year long with harvesting time of 39-45 days post tree cutting. Natural cultivation is more successful compared to the artificial one. Sago larva contains 13.80% protein, 18.04% fat and essential amino acids. Sago larva is expected to be used as source of proteins to substitute fish meal. Key word: Cultivation, sago larva, Moluccas. Luas areal tanaman sagu di Maluku 31.360 ha dengan jumlah pohon sagu siap panen sebanyak 86 pohon per ha. Salah satu limbah dari hasil panen sagu adalah batang bagian pucuk pohon yang tidak dimanfaatkan, dan tempat bertelurnya kumbang merah kelapa (Rhynchophorus ferrugenesis). Larva dari kumbang ini dikenal dengan ulat sagu, yang biasanya dikonsumsi oleh masyarakat Maluku dan Papua. Apabila ulat sagu menjadi dewasa akan berubah menjadi kumbang kelapa, yang merupakan hama pada tanaman kelapa. Pengkajian besarnya potensi dan teknik budidaya telah dilakukan pada tahun 2006 dengan tujuan: 1) mendapatkan teknik budidaya secara alami dan buatan (artifisial), 2) musim dan waktu pemijahan, 3) besarnya potensi dan nilai gizi ulat sagu. Perkiraan besarnya potensi didapat dari survei di sentra-sentra pengolahan sagu di Maluku pada Kab Maluku Tenggara, Kab Maluku Tengah dan Seram Bagian Barat. Sedangkan teknik budidaya dibedakan secara alami dan buatan (artifisial). Pengujian laboratorium dilakukan untuk mendapatkan nilai gizi dan kandungan asam amino esensial. Uji statistik dilakukan pada data hasil perbandingan perlakuan. Hasilpengkajian menunjukan berdasarkan ketersediaan luas areal tanaman sagu di Maluku, potensi ulat sagu diperkirakan sebesar 935 t, dengan produktivitas 2,52 kg/m'. Musim pemijahan sepanjang tahun dengan waktu panen 39-45 hari dari pasca tebang pohon. Budidaya secara alami lebih berhasil dibandingkan dengan cara buatan (artifisial). Ulat sagu memiliki kandungan protein 13,80%, lemak 18,04% dan asam amino esensial. Ulat sagu diharapkan dapat dipakai sebagai sumber protein pada pembuatan pakan sebagai pengganti tepung ikan. Kata kunci: Budidaya, ulat sagu, Maluku